TRÁFICO DE SERES HUMANOS NA FRONTEIRA BRASIL-BOLÍVIA: PREVENÇÃO, COMBATE E REDES DE PROTEÇÃO ÀS VÍTIMAS - NADIA CRISTINA BUREMAN (2024)
Human trafficking on the border between Corumbá (Brazil) and Puerto Quijarro (Bolivia) involves various forms of exploitation, such as forced labor, sexual exploitation, and organ trafficking. This study aims to analyze the dynamics of human trafficking on the border between these cities, considering the sociopolitical, economic, and cultural factors influencing this issue. To this end, normative frameworks associated with trafficking at the international, regional, and national levels were identified and systematized, understanding their relevance and specific application in the border region. Additionally, strategies, policies, and measures implemented at the border to prevent, combat, and respond to human trafficking were analyzed, focusing on the protection and guarantee of victims' rights. The adopted methodology included a bibliographic and documentary review, using an exploratory and descriptive approach to identify nuances, variables, and interactions documented in the literature on border studies. The research adopted a longitudinal temporal perspective, allowing for an understanding of changes, trends, and evolutions over time, especially concerning strategies for prevention, combat, and victim protection in the region. The results reveal that collaboration between Brazil and Bolivia, along with the involvement of international organizations and civil society, is crucial to combating this crime. The development of a booklet on the network to combat human trafficking on the Brazil-Bolivia border can provide clear information about risks and prevention methods, involving collaborative efforts among governments, non-governmental organizations, and civil society.